FINANCIAL RESTATEMENT AFFECTING FACTORS ANALYSIS ON INDONESIA MANUFACTURING COMPANIES - Marjono, Cornelia Clarissa; Lindrawati, Lindrawati (Jurnal Akuntansi Kontemporer, 2021)
Research Purposes. The purpose of this research is to examine and analyze the influence of corporate governance, ownership structure, financial performance, audit quality, related party transaction, and founders on board towards financial restatement of Indonesia manufacturing companies.Research Methods. The design of this research is a quantitative research. The objects of this research are Indonesia Stock Exchange manufacturing companies of 2013-2017. Data analysis technique used in this research is logistic.Research Results and Findings. The result of this research shows that corporate governance represented by board of commissioner positively affect financial restatement, board of director negatively affect financial restatement, while independent commissioner and audit committee have no effect towards financial restatement. Ownership structure has no effect towards financial restatement. Financial performance, audit quality, and related party transaction also have no effect towards financial restatement. While, founders on board positively affect financial restatement.